Complex imprint of air pollution in the basal area increments of three European tree species - Oulehle, Filip; Kolář, Tomáš; Rybníček, Michal; Hruška, Jakub; Büntgen, Ulf; Trnka, Miroslav (The Science of the total environment, 2024)
The impact of atmospheric pollution on the growth of European forest tree species, particularly European beech, Silver fir and Norway spruce, is examined in five mesic forests in the Czech Republic. Analyzing of basal area increment (BAI) patterns using linear mixed effect models reveals a complex interplay between atmospheric nitrogen (N) and sulphur (S) deposition, climatic variables and changing CO2 concentrations. Beech BAI responds positively to N deposition (in tandem with air CO2 concentration), with soil phosphorus (P) availability emerging as a significant factor influencing overall growth rates. Fir BAI, on the other hand, was particularly negatively influenced by S deposition, although recent growth acceleration suggests growth resilience in post-pollution period. This fir growth surge likely coincides with stimulation of P acquisition following the decline of acidic pollution. The consequence is the current highest productivity among the studied tree species. The growth dynamics of both conifers were closely linked to the stoichiometric imbalance of phosphorus in needles, indicating the possible sensitivity of exogenous controls on nutrient uptake. Furthermore, spruce BAI was positively linked to calcium availability across sites. Despite enhanced water-use efficiency under elevated CO2, spruce growth is constrained by precipitation deficit and demonstrates weakening resilience to increasing growing season air temperatures. Overall, these findings underscore the intricate relationships between atmospheric pollution, nutrient availability, and climatic factors in shaping the growth dynamics of European forest ecosystems. Thus, incorporating biogeochemical context of nutrient availability is essential for realistic modelling of tree growth in a changing climate.
Keywords: Picea; Trees; CO(2); Abies; Nitrogen; dusík; Nutrient stoichiometry; Forests; lesy; stromy; fosfor; Environmental Monitoring; Productivity; Acidification; Air Pollution; Air Pollutants; Tree-ring; jedle; látky znečišťující vzduch; monitorování životního prostředí; Central Europe; Phosphorus; Eutrophication; buk (rod); Climate; Czech Republic; znečištění ovzduší; smrk; Česká republika; Fagus